Hands-On Computer Vision with Julia : Build Complex Applications with Advanced Julia Packages for Image Processing, Neural Networks, and Artificial Intelligence. - Cudihins, Dmitrijs (Packt Publishing Ltd, 2018)
This book is a thorough guide for developers who want to get started with building computer vision applications using Julia. Julia is well suited to image processing because of its ease of use and the fact that it lets you write easy-to-compile and efficient machine code.